2007
DOI: 10.1016/j.brainres.2007.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular monoamine transporter 2 regulates the sensitivity of rat dopaminergic neurons to disturbed cytosolic dopamine levels

Abstract: A B S T R A C TAn abnormal accumulation of cytosolic dopamine resulting in reactive oxygen species and dopamine-quinone products may play an important role in the rather selective degeneration of substantia nigra pars compacta (SNc) dopaminergic neurons in Parkinson's disease. The neuronal-specific vesicular monoamine transporter (VMAT2), responsible for uptake of dopamine into vesicles, has been shown to play a central role both in intracellular dopamine homeostasis and sequestration of dopaminergic neurotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 59 publications
8
74
0
1
Order By: Relevance
“…Also, it has been shown that women who possess VMAT2 promoter variants which increase vesicular dopamine uptake are relatively protected from late-onset Parkinson's disease (Glatt, et al 2006). Furthermore, a recent study reported two intriguing findings: that reducing VMAT2 in midbrain cultures by shRNA leads to terminal loss and that increasing VMAT2 expression by the use of viral vectors in PC-12 cells attenuates METH cytotoxicity (Vergo, et al 2007). However, no studies investigating the consequence of elevated VMAT2 on METH neurotoxicity in vivo have yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been shown that women who possess VMAT2 promoter variants which increase vesicular dopamine uptake are relatively protected from late-onset Parkinson's disease (Glatt, et al 2006). Furthermore, a recent study reported two intriguing findings: that reducing VMAT2 in midbrain cultures by shRNA leads to terminal loss and that increasing VMAT2 expression by the use of viral vectors in PC-12 cells attenuates METH cytotoxicity (Vergo, et al 2007). However, no studies investigating the consequence of elevated VMAT2 on METH neurotoxicity in vivo have yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…METH neurotoxicity depends on the transporter proteins that package and recycle dopamine and PACAP38 has been suggested to alter this transport (Fumagalli, et al 1998, Takei, et al 1998, Fumagalli, et al 1999, Vergo, et al 2007). Dysfunction of the dopamine transporter (DAT) and the vesicular monoamine transporter 2 (VMAT2) caused by METH leads to a loss of dopamine from the neuron and oxidative stress Hastings 1999, Miyazaki, et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were transformed using the calcium-phosphate precipitation method. For this, a mixture of 27 µg lentiviral vector (Leander Johansen et al, 2005), 12 µg pMDG (envelope vector, http://www.addgene.com), 19 µg pBRΔ8.91 (packaging vector) (Vergo et al, 2007;Scholz et al, 2011), and 215 µl 2 M CaCl2 in a total volume of 1.75 ml was added dropwise to a 2x HBS solution (50 mM HEPES, 280 mM NaCl, and 1.5 mM Na2HPO4; pH 6.95) while vortexing. Precipitation was allowed by incubating the mixture at RT for 35 min.…”
Section: Lentivirus Production and Generation Of Stably Expressing Lumentioning
confidence: 99%
“…The causal link between cytosolic DA levels and METH toxicity is supported by several studies. In fact, overexpression of VMAT2, which stores DA in the vesicles, significantly protects PC12 against METH toxicity [165], while a mutant strain of mice, which possesses only 5-10% of the VMAT2 expressed by wild-type animals, undergo enhanced METH-induced striatal neurotoxicity [166]. For the same reasons, DAT inhibitors protect against METH-induced striatal DA damage [74, 83, 167].…”
Section: Methamphetamine-induced Dopaminergic Toxicitymentioning
confidence: 99%